2016
DOI: 10.1152/japplphysiol.00540.2015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative fuel selection and shivering thermogenesis during a 12- and 24-h cold-survival simulation

Abstract: Because the majority of cold exposure studies are constrained to short-term durations of several hours, the long-term metabolic demands of cold exposure, such as during survival situations, remain largely unknown. The present study provides the first estimates of thermogenic rate, oxidative fuel selection, and muscle recruitment during a 24-h cold-survival simulation. Using combined indirect calorimetry and electrophysiological and isotopic methods, changes in muscle glycogen, total carbohydrate, lipid, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In theory, under compensable conditions, T core can be maintained as long as cold-induced H prod is sustained. For example, during mild cold exposure in a thermal chamber at 7.5 C, we showed that T core , H prod and ST intensity at »1.8 xRMR can be sustained in men for up to 24 h independently of a negative energy balance (»44% less than 24 h energy demand) and independently of a substantial change in metabolic fuel utilization 65 (see also Metabolic requirements of ST). However, it remains that even under this compensable condition, only four of the eight recruited subjects were willing to remain in the cold for the full 24 h. This exemplifies that the challenges for human survival even under mild, compensable conditions extend far beyond sustaining adequate thermogenic and physiologic responses.…”
Section: Contribution Of St To Total Heat Productionmentioning
confidence: 78%
See 1 more Smart Citation
“…In theory, under compensable conditions, T core can be maintained as long as cold-induced H prod is sustained. For example, during mild cold exposure in a thermal chamber at 7.5 C, we showed that T core , H prod and ST intensity at »1.8 xRMR can be sustained in men for up to 24 h independently of a negative energy balance (»44% less than 24 h energy demand) and independently of a substantial change in metabolic fuel utilization 65 (see also Metabolic requirements of ST). However, it remains that even under this compensable condition, only four of the eight recruited subjects were willing to remain in the cold for the full 24 h. This exemplifies that the challenges for human survival even under mild, compensable conditions extend far beyond sustaining adequate thermogenic and physiologic responses.…”
Section: Contribution Of St To Total Heat Productionmentioning
confidence: 78%
“…Under conditions previously describe in glycogen depleted and glycogen loaded individuals, 68 the model of Wissler predicts that shivering at 200 W could be sustained for 33 to 42 h. In addition, Tikuisis et al 74 later suggested that the Wissler model may underestimate true values. In a more recent paper, Haman et al 65 estimated a 20 h time to glycogen depletion based on whole-body oxidation of glycogen; a value clearly shorter than that predicted by Wissler et al 67 or Tikuisis et al. 74 Again, calculations of ST endurance based on time to glycogen depletion have two possible shortcomings: (1) glycogen may not be essential, and low-intensity shivering is sustainable solely on lipids and proteins and/or, (2) a significant shift in fuel selection to spare glycogen takes place after 2 h of shivering (in fact, a progressive increase in fat oxidation was observed by Tikuisis et al 74 during prolonged shivering lasting for up to 4 h).…”
Section: Metabolic Requirements Of Stmentioning
confidence: 97%
“…During shivering, heat is primarily produced by the major ATP utilizing enzymes including Na + /K + ATPase, myosin ATPase and SERCA [1214]. Interestingly, it has been shown that mice and humans can maintain body temperature during acute cold exposure, even when shivering is minimized [8, 15]. Studies have also shown that during cold acclimation, shivering is gradually replaced by nonshivering thermogenesis (NST) .…”
Section: Muscle As a Thermogenic Organ- A Historic Accountmentioning
confidence: 99%
“…This is because repetitive muscle contractions during constant shivering can cause muscle damage [16]. In addition, high intensity shivering relies predominantly on muscle glycogen that can become limiting after few hours [15]. …”
Section: Muscle As a Thermogenic Organ- A Historic Accountmentioning
confidence: 99%
“…BAT, a nonshivering thermogenesis, is distributed in mouse body, including interscapular, periaortic, perirenal and intercostal region [1]. Skeletal muscles increase the metabolic heat by involuntary and rhythmic contraction, known as shivering thermogenesis organ [2]. Coordination of these organs is necessary to maintain metabolic process in vital organ during cold exposure.…”
Section: Introductionmentioning
confidence: 99%